Armando Petrucci en España. A propósito de un nuevo “libro misceláneo” - Gozalbo Gimeno, Daniel (Scrineum, 2013)
This article takes advantage of the translation and publication in Spanish of some key texts by Armando Petrucci concerning the production of writing from the Antiquity to the contemporary world and it aims to revise the main methodological contributions carried out by this eminent Italian paleographer throughout his professional career. Furthermore, this paper intends to give some reflections on the influence of Petrucci’s work upon the contemporary Spanish academic world and more especially in the field of the History of Written Culture while developing at the same time some research tasks on a topic that has not been tackled yet in Spain . Last but not least, it is taken into account Petrucci’s reflection on the institutions in charge of preserving the memory of the past in democratic societies and his definition of an Archive as a dynamic complex to make some remarks regarding the public function of Spanish Archives and the necessity of approaching them from a historical perspective.